METHODS OF FORMATION OF ENTEROLOGY TERMS WITH COMPONENT ENTER (O) – - Телеки, Мария (Modern engineering and innovative technologies, 2022)
Absract. On the material of Latin and English languages, methods of word formation and ways of derivation of terminological units with the enter (o) - component are highlighted. It has been established that for the formation of compound terms, stems which